Beneficial Effect of Zinc on diabetes induced kidney damage and liver stress oxidative in rats - Derouiche, Samir; Manel, Djermoune; Kawther, Abbas (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
The present study was designed to investigate the effects of Zn supplementation on kikney function and liver oxidative stress in Alloxan diabetic rats. Male albino Wistar rats were randomly divided into 4 groups (n=10): Control, Non Diabetic + zinc, Diabetic and Diabetic + Zinc. Diabetes was induced by alloxan (150 mg/kg). Zinc (231 mg/kg feed) as ZnSO4 7H2O was added to the feed of the animals in the zinc groups for 21 days. Alloxan Diabetes caused a significant decrease in body weight gain, serum and tissue zinc, serum protein concentrations, liver GSH, GPx and GST activities .In contrast, it led to an augmentation in urea, creatinine, uric acid and MDA in rats. Zinc supplementation in the diet for diabetic rats ensured a partial correction of the previous parameters. In conclusion, this study indicated that zinc act as powerful antioxidants which may exercise adverse effect against severity and complication of diabetes.